2011
DOI: 10.1158/1538-7445.am2011-2752
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2752: Genetic heterogeneity of ovarian cancer survival effects in BRCA1/2 germline mutations: a large, multi-center study

Abstract: Rare germline mutations in the breast and ovarian cancer predisposition genes BRCA1 and BRCA2 are present in roughly 5 percent of ovarian cancer patients. Both genes play key roles in DNA damage repair but appear to have distinct, although often complementary, functions. The risks of breast and ovarian cancer have been shown to differ between BRCA1 and BRCA2 carriers, and mutation-specific effects have also been suggested for both groups. Published reports comparing the survival of ovarian cancer patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A recent report on patients from 27 international studies demonstrated improved survival of BRCA1 and BRCA2 mutation carriers relative to non-carriers. 57 Unlike previous series (and the current case series) where the number of BRCA1 and BRCA2-null patients from which conclusions were drawn was relatively small, Bolton's multi-center study had outcome data on over 1400 BRCA1 and BRCA2 mutation carriers and B2400 non-carriers, allowing them to take into account clinical factors known to influence outcome. The recently published data from The Cancer Genome Atlas has confirmed the association of BRCA mutations with a favorable prognosis, and also showed no prognostic effect with BRCA1 promoter methylation (compared with tumors lacking BRCA mutations or methylation).…”
Section: Discussionmentioning
confidence: 98%
“…A recent report on patients from 27 international studies demonstrated improved survival of BRCA1 and BRCA2 mutation carriers relative to non-carriers. 57 Unlike previous series (and the current case series) where the number of BRCA1 and BRCA2-null patients from which conclusions were drawn was relatively small, Bolton's multi-center study had outcome data on over 1400 BRCA1 and BRCA2 mutation carriers and B2400 non-carriers, allowing them to take into account clinical factors known to influence outcome. The recently published data from The Cancer Genome Atlas has confirmed the association of BRCA mutations with a favorable prognosis, and also showed no prognostic effect with BRCA1 promoter methylation (compared with tumors lacking BRCA mutations or methylation).…”
Section: Discussionmentioning
confidence: 98%
“…It is not clear whether age at diagnosis in ovarian cancer patients who harbor BRCA 1/BRCA 2 pathogenic/likely pathogenic variants differs from non-carriers. It was shown that BRCA1 pathogenic/likely pathogenic variant ovarian cancer patients were younger compared with non-carriers, but it was not observed for BRCA2 carriers [25]. Another study showed that age at diagnosis in ovarian cancer patients who harbor the BRCA 1/BRCA 2 pathogenic/likely pathogenic variant was comparable to non-carriers [27].…”
Section: Discussionmentioning
confidence: 99%
“…BRCA 1/BRCA 2 pathogenic/likely pathogenic variant status affects both progression-free survival and overall survival [24]. Firstly, it was shown that ovarian cancers in BRCA 1/BRCA 2 pathogenic/likely pathogenic variant carriers had favorable survival outcomes, compared with non-carrier patients [25][26][27]. Platinium sensitivity, repeatedly responded to platin-based regimens and longer duration of response, might play important role in favorable survival advantage in BRCA 1/BRCA 2 carriers with ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%